Theoretical Insights on Solvent Control of Intramolecular and Intermolecular Proton Transfer of 2-(2′-Hydroxyphenyl)benzimidazole - Prommin C. (2017)
© 2017 American Chemical Society. Excited-state proton transfer (ESPT) processes of 2-(2′-hydroxyphenyl)benzimidazole (HBI) and its complexation with protic solvents (H 2 O, CH 3 OH, and NH 3 ) have been investigated by both static calculations and dynamics simulations using density functional theory (DFT) at B3LYP/TZVP theoretical level for ground state (S 0 ) and time-dependent (TD)-DFT at TD-B3LYP/TZVP for excited state (S 1 ). For static calculations, absorption and emission spectra, infrared (IR) vibrational spectra of O-H mode, frontier molecular orbitals (MOs), and potential energy curves (PECs) of proton transfer coordinate were analyzed. Simulated absorption and emission spectra show an agreement with available experimental data. The hydrogen bond strengthening in the S 1 state has been proved by the changes of IR vibrational spectra and bond parameters of the hydrogen moiety with those of the S 0 state. The MOs provide the visual electron density redistribution confirming the hydrogen bond strengthening mechanism. The PECs show that the proton transfer (PT) process is easier to occur in the S 1 state than the S 0 state. Moreover, on-the-fly dynamics simulations of all systems were carried out to provide the detailed information on time revolution. The results revealed that the excited-state intermolecular proton transfer for HBI is fast, whereas the excited-state intermolecular proton transfer for HBI with protic solvents are slower than that of HBI because the competition between intra- and intermolecular hydrogen-bonds between HBI and protic solvent. These intermolecular hydrogen-bonds hinder the formation of tautomer, hence explaining the low quantum yield found in the protic solvent experiment. Especially for HBI complexing with methanol, only ESIntraPT occurs with small probability compared to HBI with water and ammonia.